Increasing the Students’ Social Intelligence through Extracurricular Pencak Silat - saripudin, ahmad arip (International Journal Pedagogy of Social Studies, 2018)
The purposes of the study are to discover the general condition of students’ social intelligence before join the extracurricular, to know the implementation of the extracurricular in fostering students, and to find out Pencak Silat’s contribution in increasing students’ social intelligence.